1996
DOI: 10.1212/wnl.47.1.237
|View full text |Cite
|
Sign up to set email alerts
|

GM1b is a new member of antigen for serum antibody in Guillain-Barre syndrome

Abstract: Serum antibody from some patients with Guillain-Barré syndrome recognized an antigen of a minor component in human brain monosialoganglioside fraction. We purified that antigen, which migrated at a position slightly lower than that of GM1 on a thin-layer chromatogram (TLC), by using Iatrobeads column chromatography and preparative TLC. Structural analyses, including fast atom bombardment mass spectrometry, showed it to be GM1b. An enzyme-linked immunosorbent assay (ELISA) using purified GM1b showed that anti-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 13 publications
1
54
0
1
Order By: Relevance
“…Some investigators suggest that the presence of anti-GM 1 antibodies in GBS is a marker for the AMAN form of the disease and signifies poor recovery [24][25][26][27][28][29][30], a view not shared by others [31,32]. Yuki et al have described antibodies to a wide range of minor gangliosides in Japanese patients [33][34][35] and, in agreement with other studies, found anti-GM 1b antibodies in 35% of GBS patients [35][36][37].…”
Section: Anti-ganglioside Antibodies In Gbssupporting
confidence: 63%
See 1 more Smart Citation
“…Some investigators suggest that the presence of anti-GM 1 antibodies in GBS is a marker for the AMAN form of the disease and signifies poor recovery [24][25][26][27][28][29][30], a view not shared by others [31,32]. Yuki et al have described antibodies to a wide range of minor gangliosides in Japanese patients [33][34][35] and, in agreement with other studies, found anti-GM 1b antibodies in 35% of GBS patients [35][36][37].…”
Section: Anti-ganglioside Antibodies In Gbssupporting
confidence: 63%
“…Immunization of mouse with GT 1a -containing LPS can produce a serum with anti-GQ 1b antibody and the antibodies were demonstrated to induce the release of acetylcholine, followed by complement-mediated conduction block [126]. In addition, GD 1b immunization has produced sensory ataxic neuropathy in rabbits characterized by axonal degeneration and macrophage infiltration [36]. This is the first established animal model of an antibody-mediated autoimmune neuropathy caused by an immune response to gangliosides.…”
Section: Models Of C Jejuni-associated Gbsmentioning
confidence: 95%
“…Autoantibody to GM1b has been shown to be a useful diagnostic marker of GBS, 72 and anti-GM1b IgG antibody was found to be associated with GBS after C. jejuni enteritis. 145 Of 132 patients with GBS, 19% had anti-GM1b antibody.…”
Section: A True Case Of Molecular Mimicrymentioning
confidence: 99%
“…35 Immunization with GD1b induces an ataxic sensory neuropathy in rabbits. 63 Moreover, Willison et al 113,115 reported that a monoclonal antibody against GQ1b immunostained the DRG and ocular muscle spindles, suggesting that these structures are the targets of an immunological reaction. More recent studies 83 have also suggested a role for anti-GQ1b antibodies in mediating nerve terminal injury, demonstrating that the neuromuscular junction may be an additional target.…”
Section: Acute Autoimmune Ataxic Syndromesmentioning
confidence: 99%